High Performance Sheet of PBX based on NTO. Issue 1 (1st August 2022) - Elbeih, Ahmed; Elnogomy, Mohamed; Elshenawy, Tamer; Saleh, Ahmed; Azazy, Ahmed; Hussein, Ahmed k.; Zaky, M. G.; Ahmed, Hesham S.
Abstract: 3-nitro-1, 2, 4-triazol-5-one (NTO) is a low sensitive high explosive which has been used in the formation of low sensitive ammunitions. In this study, the preparation method of NTO explosive was discussed. A sheet of PBX on the basis of NTO bonded by HTPB binder matrix was prepared (NTO-PBX). The formulation is investigated for explosive properties to understand the influence of NTO on the performance of the PBX sheet. Impact and friction sensitivities of NTO-PBX, heat of Combustion and Detonation velocity were specified. EXPLO5 code, version 5.04, was utilized to calculate the theoretical detonation characteristics of NTO-PBX. For comparison, Data-sheetC, EPX-1, Semtex 1A and Formex P1, were also studied. By comparing the obtained results, confirmation of some relationships was investigated. The detonation velocity of the NTO sheet explosive was the highest of all the studied samples. The experimental and calculated results of NTO-PBX and the other compositions are in a good agreement.